1986
DOI: 10.1037/0735-7028.17.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Challenge of computers in psychological assessment.

Abstract: At a 1984 APA Division 5 symposium, James Mitchell argued that "the advent of computer-based test interpretation" . . . "presents the field of psychology with its most serious and consequential challenge of the next decade; how we react to that challenge 44 This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. HARVEYA. SKINNER received his doctorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…Many clinicians resist the use of computers in the diagnostic process on the basis of arguments that are seldom made explict (Skinner & Pakula, 1986). Although clinicians indicated that they did not ask patients primarily because of the psychological condition of the patients, no significant differences between nonsolicited and solicited patients in the nature or extent of psychopathology were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinicians resist the use of computers in the diagnostic process on the basis of arguments that are seldom made explict (Skinner & Pakula, 1986). Although clinicians indicated that they did not ask patients primarily because of the psychological condition of the patients, no significant differences between nonsolicited and solicited patients in the nature or extent of psychopathology were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many advantages to such a procedure (Denner, 1977;Reynolds, McNamara, Marion, & Tobin, 1985;Space, 1981), several potential problems also exist. Specifically, concern has been expressed that computerized test administration is not necessarily equivalent to paper-andgencil administration (Hartman, 1986;Hofer & Green, 1985;Matarazzo, 1983;Skinner & Pakula, 1986). These authors caution, therefore, that it may not be appropriate to compare test scores based on an automated assessment to norms that have been established using a paperand-pencil format.…”
Section: Please Scroll Down For Articlementioning
confidence: 95%
“…Previous research has indicated that computeradministered health and psychological surveys generally have good psychometric properties when compared to the same survey administered by paper and pencil (Miller et al, 2002;Skinner & Pakula, 1986). However, Butcher, Perry, and Atlis (2000) reviewed the equivalence of assessment methods in psychiatric screening, personality, neuropsychology, and personnel Psychology Downloaded by [University of New Hampshire] at 06:46 02 November 2014 psychology and found the comparability of computerized and standard administration measures to vary.…”
mentioning
confidence: 93%